Manajemen Humas dalam Upaya Meningkatkan Mutu Pendidikan Perguruan Tinggi - Muhammad Iqbal (Jurnal Humaniora dan Ilmu Pendidikan, 2023)
Public Relations Management is an important part that can be used in improving the quality of quality in tertiary institutions. Purpose: This article was created with the aim of knowing and analyzing how Public Relations Management improves the quality of Higher Education. Methodology: The method used in compiling this article is literature study, namely research that uses the results of reviews from other journals. Results: From these results it is known that Public Relations Management must carry out: (1) Public Relations Management must maximize 4 strategic roles, namely as expert advisers, problem solvers, communication facilitators, communication technical implementers. (2) Implementation and communication of Public Relations Management must be actual, factual, and proficient in using communication tools/media that help Public Relations Management work better. (3) the evaluation of Public Relations Management aims to analyze the deficiencies and what needs to be improved by the Public Relations Management.